Radar talks : Phil Balagtas on futures design and thinking - Balagtas, Phil (O'Reilly Media, Inc., 2022)
As the craft of creation continues to evolve and require more strategic thinking, we must also evolve our mindset and tools to address today's greatest political, social, environmental, and cultural challenges. Futures design and thinking provides a set of tools that can prepare us for the ever-changing landscape of the future and enable us to better assess the challenges of emerging technologies, climate change, and the implications of dynamic social structures. In this edition of Radar Talks, Design Futures Initiative founder Phil Balagtas takes a deep dive into the futures design and thinking methodology. You'll learn how to use futures thinking as a strategic tool to uncover threats and opportunities on the near and distant horizon. Recorded on January 10, 2022. See the original event page for resources for further learning or watch recordings of other past events. The O'Reilly Radar Talks series brings you expert opinions on emerging topics through hour-long interactive events. In conversation with some of the industry's top minds, you'll look at the early signals indicating significant trends and new technologies that will shape the future--and discover how to begin forging these technologies now. Share your own predictions and ask your questions while gaining insight into our experts' unique outlooks for the future.